TASK SYNCHRONIZATION IN WIRELESS DISTRIBUTED NETWORKS USING A SHARED-CLOCK ARCHITECTURE - Muhammad Amir,; Bilal Ur Rehman,; Kifayat Ullah,; Muhammad Farooq,; Humayun Shahid,; Muhammad Iftikhar Khan, (Spectrum of Engineering Sciences, 2025)
Safety-critical embedded systems should exhibit robustness and fault tolerance. Shared-clock (S-C) scheduling architectures have been developed to encapsulate the above qualities in resource-constrained distributed systems which employ a time-triggered (TT) architecture. Previous work in this area has targeted ‘wired’ communication mediums (e. g. local connections based on CAN). In this paper we begin to consider whether S-C architecture can be adapted for use in wireless environments. This work is at an early stage and the main aims of the paper are: (1) to explain the operation of wired S-C designs; (2) to summarize the problems which are faced when attempting to use a S-C algorithm in a wireless environment; (3) to present some initial suggestions for ways in which a S-C algorithm might be adapted for use in a wireless environment; (4) to describe the design of a testbed which will be used to support further research in this area.